Seismic design method analyses of an innovative steel damping bearing for railway bridges. (15th July 2018) - Liu, Cong; Gao, Ri; Guo, Bo
Highlights: A novel steel damping bearing consisted of pot bearing and steel dampers is developed. Mechanical theory calculation of the steel damping bearing is presented. Shaking table tests are conducted to evaluate the effectiveness of the design methods. Design methods are also analyzed by numerical calculations. Abstract: The bearing sliding effect of the pot bearing and plastic deformation of a low-yield steel damper has been proven to be effective in mitigating the seismic response of railway bridges during earthquakes. However, both the sliding effect and plastic deformation require large bearing and pier dimensions to avoid unseating damage during earthquakes, leading to higher costs during construction of the railway bridge. On the basis of bearing sliding and energy dissipation, a novel steel damping bearing is developed by using "function separated design". The steel damping bearing is composed of a pot bearing to support the vertical loads and a series of low-yield steel dampers to bear the horizontal seismic loads. In this paper, both the force-based and displacement-based design methods for the steel damping bearing are analysed by using the equivalent linearization method. Then, a 1:7 scale two-span simply supported railway bridge model is tested on a shaking table under different ground motions to estimate the design method results for the steel damping bearing. Additionally, a bridge model with pot bearings is tested as a benchmark model. Finally, the prototype bridge is modelled by numerical analysis to evaluate the effectiveness of each design method. The experimental and numerical results reveal that both design methods can effectively simulate the response of the bridge model. Moreover, a comparison between the models with steel damping bearings and with pot bearings reveal that the steel damping bearing can greatly mitigate the pier forces and displacement with an acceptable displacement between the pier and girder.